Rancang Bangun Sistem Informasi Penerimaan Siswa Baru Berbasis Web Pada Yayasan Bina Anak Mandiri Bekasi - Wijaya, Ganda; Herlina, Maria; Olivia, Shinta; Suhardjono, Suhardjono (APMMI - Asosiasi Profesi Multimedia Indonwsia, 2019)
Abstract â€“ The development of information systems until now is so rapid, even so many people around the world depend on developing technology. Including the new student admission process carried out by several schools, where currently there are still educational institutions or schools in implementing new student admissions manually, including the Bina Anak Mandiri Foundation, is an organization engaged in kindergarten (TK) school education , starting from the acceptance of new students, and making reports still using a manual system. In providing the best service for prospective student parents and providing convenience for staff in KEMAS Kindergarten, a new student admission information system and computerized and web-based tuition fees are needed. The purpose of the research was done so that KEMAS Kindergarten and prospective student parents were easier, more effective and efficient in implementing SPP registration and payment using the web. The method used is more directed to observation with the waterfall model. With the construction of this system, the work of staff and parents of prospective students is easier, especially in the process of registering new students at KEMAS Kindergarten. Â Keywords: Acceptance of New Students, Information Systems